2011
DOI: 10.1111/j.1464-410x.2011.10159.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin use on biochemical outcome following radical prostatectomy

Abstract: Study Type – Prognosis (retrospective cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? Statin use may reduce the risk of developing prostate cancer. Studies also suggest that the protective effect of statins may be beneficial for prostate cancer patients following treatment. Statin users may also have lower PSA than non‐users. Our study agrees with the findings that statin users may have lower PSA than non‐users. Contrary to the findings that statins are protective in pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
2
33
1
1
Order By: Relevance
“…Only one study found a dose-dependent reduction of the biochemical recurrence risk [22], while three others reported that there was no statistically significant association [11,20,23]. Ritch et al [24] had similar findings as our series. They reported a statistically significant higher rate of >7 Gleason score and that statin use was an independent predictor of BCR (HR 1.54, p < 0.05).…”
Section: Discussionsupporting
confidence: 84%
“…Only one study found a dose-dependent reduction of the biochemical recurrence risk [22], while three others reported that there was no statistically significant association [11,20,23]. Ritch et al [24] had similar findings as our series. They reported a statistically significant higher rate of >7 Gleason score and that statin use was an independent predictor of BCR (HR 1.54, p < 0.05).…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, Ritch et al (21) conducted a similar retrospective analysis of 1261 patients treated with radical prostatectomy. Statin users represented 22% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ritch et al detected an increased risk of BCR in PC patients using statins after RP. 16 In patients classified as D'Amico low-risk category, those taking statins had a significantly shorter BCR-free survival than patients not taking statins. In contrast, statin users in the intermediate and high-risk categories had no significant difference in BCR compared with non-users.…”
Section: Discussionmentioning
confidence: 95%
“…This is further supported by a significantly higher rate of patients with a pathological Gleason sum X7 in statin users compared with non-statin users in the study cohort. 16 In addition, another study showed a significantly lower PSA in patients using statins and Gleason sum X7. 12 However, it may be questioned if a PSA reduction is the explanation for the unfavorable outcome of statin users in the study because the rate of patients with a pathological Gleason sum X7 was also higher in the group of statin users in a study that found statin use to be associated with favorable outcome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation